2012
DOI: 10.1111/j.1600-0579.2012.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational needs in the field of detection of domestic violence and neglect: the opinion of a population of French dentists

Abstract: More information and training concerning abuse and domestic violence is required in the French undergraduate dental curriculum in order to help practitioners deal with such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 25 publications
4
49
0
1
Order By: Relevance
“…The literature indicates that <11% of the dentists interviewed in scientific surveys suspected of EA. These findings are different from the current panorama – suggesting that EA has a low prevalence rate.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The literature indicates that <11% of the dentists interviewed in scientific surveys suspected of EA. These findings are different from the current panorama – suggesting that EA has a low prevalence rate.…”
Section: Discussionmentioning
confidence: 56%
“…lesions with EA is related closely to the level of education and training in the field. The articles addressed in the present systematic literature review indicated a range of 47-93.9% of dentists that never received information on EA during undergraduation and graduation courses 5,6,19 , contrasting with the small amount (8.3-11%) of dentists that received 20,21,23 . McDowell et al 18 reported that 78% of the dentists revealed the need and interest for having more information on EA.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Though the rate is lower than similar surveys conducted in Norway (61.3%) [Vidnes-Kopperud et al, 2011], the USA (57%) [Gordan et al, 2010] or Japan (67%) [Kakudate et al, 2012], it is typical of medical and dental questionnaire surveys in France, where, in a selection of recent studies, the response rate ranged from 16.6% to 54% [Bangerter et al, 2009;Benhamou et al, 2012;Drigeard et al, 2012;Herlin et al, 2008;Valgueblasse et al, 2012]. Nevertheless, the general demographic characteristics of the 2002 and 2012 respondents reflect well those of the French populations of GPs at the time of each study (Conseil de l'Ordre des Chirurgiens-Dentistes, France), allowing the authors to stipulate, despite the relatively low response rate, that the present results might be representative of the French GPs' attitudes towards the diagnosis and management of occlusal caries lesions.…”
Section: Discussionmentioning
confidence: 88%
“…Dentists and dental hygienists are in a unique position to notice symptoms of child maltreatment, as 50 to 70% of all abused children have visible injuries on the head or in the neck region (Cairns, Mok, & Welbury, 2005a;Jesse, 1995;Welbury & Murphy, 1998). However, previous studies indicate a lack of knowledge in the professional dental teams on how to handle suspicions, including barriers and lack of knowledge about procedures for reporting such suspicions (Brattabo, Iversen, Astrom, & Bjørknes, 2016;Cairns, Mok, & Welbury, 2005b;Cukovic-Bagic et al, 2015;Drigeard, Nicolas, Hansjacob, & Roger-Leroi, 2012;Hashim & Al-Ani, 2013;Kaur et al, 2016;Laud, Gizani, Maragkou, Welbury, & Papagiannoulis, 2013;Mogaddam, Kamal, Merdad, & Alamoudi, 2016;Owais, Qudeimat, & Qodceih, 2009;Uldum, Christensen, Welbury, & Poulsen, 2010;Uldum, Christensen, Welbury, & Haubek, 2017). The available reports on this topic are all conducted in large-scale societies, but one of these (Brattabo et al, 2016) showed that public dental health personnel working in smaller municipalities (≤ 10,000 inhabitants) reported suspicion of child maltreatment less frequently than dental public health personnel working in larger municipalities.…”
mentioning
confidence: 99%